Correlated, dual-beam optical gating in coupled organic-inorganic nanostructures - Wurst, Kai M.; Bender, Markus; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2018)
An optical switch with two distinct resonances is formed by combining PbS nanocrystals and the conductive polymer poly[sodium 2-(2-ethynyl-4-methoxyphenoxy)acetate] (PAE) into a hybrid thin film. Infrared excitation of the nanocrystals invokes charge transfer and consecutive polaron formation in the PAE, which activates the switch for excited-state absorption at visible frequencies. The optical modulation of the photocurrent response of the switch exhibits highly wavelength-selective ON/OFF ratios. Transient absorption spectroscopy shows that the polaron formation is correlated with the excited state of the nanocrystals, opening up new perspectives for photonic data processing. Such correlated activated absorption can be exploited to enhance the sensitivity for one optical signal by a second light source of different frequency as part of an optical amplifier or a device with AND logic.
Gesehen am 09.04.2020